If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6(4-x)=4(2-x)
We move all terms to the left:
6(4-x)-(4(2-x))=0
We add all the numbers together, and all the variables
6(-1x+4)-(4(-1x+2))=0
We multiply parentheses
-6x-(4(-1x+2))+24=0
We calculate terms in parentheses: -(4(-1x+2)), so:We get rid of parentheses
4(-1x+2)
We multiply parentheses
-4x+8
Back to the equation:
-(-4x+8)
-6x+4x-8+24=0
We add all the numbers together, and all the variables
-2x+16=0
We move all terms containing x to the left, all other terms to the right
-2x=-16
x=-16/-2
x=+8
| 1/3(9x=30)+5=16 | | 11m-8/6=16 | | 2(x-4)=-(x-7) | | -2(1.6-3)+x=2 | | -2(1.6-3)+x=3 | | B-(0.17b)= | | 2x+15x=51 | | -9x+7=-2x-7 | | y=49+11 | | 0.4-y=-17.6 | | y=15+7 | | m/6+24=27 | | 4.0x+4=2.0x+8 | | x+2x^2+x+20x=0 | | (x+2)(x^2+x+20x)=0 | | h/10+30=35 | | -3(a−4)=-9 | | 4=m-35/9 | | 3^(2x+5)=5^(2x) | | 9+9t=72 | | 90=38.43+0.25x | | w+11/5=7 | | 17.8+n=20 | | 4/15=-2/5a | | 10=p+16/3 | | 99=9(b+7) | | 5x-4+3x+31+4x+15+7x-64+6x-8+153+120=360 | | 9+3g=36 | | (2x+1)=360 | | 3x+7=9x+14 | | (4x+7)=360 | | 15=2n-5 |